Modos de vida enunciados nas lojas de moda esportiva na Oscar Freire: regimes de sentido e de interação nas práticas de vida de São Paulo - Barretto, Vera Lucia da Silva Azeredo Pereira (2017)
This research project sets out to investigate how brands as addressors in the sports fashion universe organize their discourses so as to exhibit new ways of life in stores. In situ observation is the basis for an endeavor to understand the discursive mechanisms — enunciatory, thematic, figurative and plastic — deployed to foster belief in these enunciations as verdictive, so that credibility leads to their being taken up as life aspirations. Discursive strategies and types of interaction are mapped, and these constructions are then systematized in a typology comprising types of interactions and types of store and consumer. The choice of stores in the sportswear segment is motivated by the action of these addressors, which transcend the role of proposing forms of dress to present contemporary ways of urban life, in a move aligned with the growing importance of everyday physical activity for people who live in São Paulo. Observation leads to a corpus consisting of four stores — Track&Field, Adidas, Nike and Asics — which together form the sports quadrilateral of Rua Oscar Freire, São Paulo’s emblematic upmarket shopping street. The theoretical and methodological foundations range from the semiotics of Greimas, particularly as developed in Landowski’s sociosemiotics, highlighting sensitivity, visibility, public versus private, and the role of interactions in the apprehension and construction of meaning; to Oliveira’s developments regarding enunciations in discursive interactions, meaning apprehended in action, esthesia, and syncretism; and the semiotic contributions to marketing, brand management and consumer behavior studies of Floch, Pezzini, Cervelli, Semprini, Ceriani, and Ciaco. The analysis of store plasticity follows research on window displays by Oliveira and Demetresco. The investigation shows that the discourses of sports brands across all communication channels evidence a certain distancing from the concept of sports linked solely to performance and a tendency to highlight values closer to people’s everyday lives such as well-being, health, fashion, and beauty. Brands in this segment enunciate ways of living that reiterate these values as lifestyles, and when these lifestyles are displayed in the valuable space of a store on an iconic street like Rua Oscar Freire they acquire prescriptive force, leading individuals to believe in the need to adopt and appropriate this axiology as essential to their participation in contemporary urban life. The study also aims to link semiotics to brand management and visual merchandising, offering a rigorous scientific framework for brand communication strategies